Neurotoxicological Effects of Some Mycotoxins on Humans Health and Methods of Neuroprotection - Aleksandra Kuć-Szymanek; Daria Kubik-Machura; Klaudia Kościelecka; Tomasz Męcik-Kronenberg; Lidia Radko (Toxins)
Food contamination with mycotoxin-producing fungi increases the risk of many diseases, including neurological diseases closely related to the neurotoxicity of these toxins. Based on the latest literature data, we presented the association of common Fusarium mycotoxins with neurological diseases. Articles from 2001 to 2024 were analyzed. The mechanisms underlying the neurotoxicity of the described mycotoxins were presented. They are mainly related to the increase in oxidative stress in neuronal cells, which leads to higher levels of pro-inflammatory cytokines as IL-1β, IL-6 and TNF-α, enzymatic activity as GST, GPx, CAT and SOD and neurotransmitter dysfunction (5-HT, serotonin, dopamine and GABA). At the end of the article, based on the literature data, we attempted to present ways to mitigate mycotoxin neurotoxicity using mainly natural substances of plant origin. The data in this review focus on the Fusarium mycotoxins most frequently found in food and will be useful as comparative information for future studies. It is important to conduct further studies to mitigate the neurotoxic effects of Fusarium mycotoxins in order to reduce the development of diseases of the nervous system.